Marie-Adélaïde de Savoie (1685-1712) - Preyat, Fabrice (2014)
In October 1696, the procession from Turin led Marie-Adélaïde de Savoie to Versailles. The marriage contract which now binds her to the Duke of Burgundy, grandson of Louis XIV, will seal, a few months later, the fate of Europe by the peace of Ryswick. From the birth of his daughter, guided by lucid cynicism, Victor Amadeus II had destined her to become a French princess. He succeeds very well. From the outset, the monarch was seduced by the extraversion, the naturalness and simplicity of the child; he found it "at will". Having become duchess of Burgundy, the young woman nevertheless upsets the etiquette of the court of France, confided in the devotions. She quickly becomes the darling of Versailles. Her temper tempers the morose religiosity of her husband; her cheerfulness galvanises around her musicians, composers, choreographers and men of letters. His enthusiasm and his casualness encourage to multiply the balls, the plays, the theatrical performances, the lotteries of chinoiseries ... The taste of the duchess is eclectic. She dances ballet-masquerade, is seduced by the magical fairy tale, touches the harpsichord with a certain talent, applauds the Italian Theater and interprets the sacred tragedies offered by Madame de Maintenon. The last years of the reign of Louis XIV were thus reborn, under the influence of expensive entertainment honored by the king, all a literary, musical, but also architectural patronage, around the work of development of the Menagerie, whose enjoyment is offered to The Duchess. The court emerges from its torpor during this pivotal time that connects the extinct splendors of the court of the Sun King with the excesses of the Regency, then of Louis XV. By illuminating his formative years, studying the patronage of the Duchess of Burgundy within the court system and a policy of distinction marked by the pregnance of several political clans, by questioning the efflorescence of funeral orations of where pierced the disappointed hopes and the collective imagination of the nation, the present volume intends to fill the gaps of contemporary historiography long remained silent on the brief destiny of Marie-Adélaïde of Savoy and the climate of the court of Versailles between 1696 and 1712.